Kinematical and EMG-classifications of a fencing attack - Frere, J.; Göpfert, B.; Nüesch, C.; Huber, C.; Fischer, M.; Wirz, D.; Friederich, N. F. (International Journal of Sports Medicine, 2011)
8 expert fencers were studied with a 3-dimensional motion analysis system. Each subject performed 10 flèche attacks toward a standardized target. Surface electromyography signals (EMG) were recorded of the deltoid pars clavicularis, infraspinatus and triceps brachii caput laterale muscles of the weapon arm. The recorded EMGs were averaged using EMG wavelet-transformation software. 4 phases were defined based on the arm kinematics and used to classify fencers into 2 groups. A first group of 4 fencers showed an early maximal elbow extension (Early MEE) whereas the second group presented a late maximal elbow extension (Late MEE). 2 EMG-classifications were based on this kinematical classification, one in the time-domain and the other in the frequency-domain by using the spherical classification. The time-domain EMG-classification showed a significantly (p=0.03) higher normalized deltoid intensity for the Early MEE group (91±18%) than the Late MEE group (36±13%) in the attack phase. The spherical classification revealed that the activity of all the muscles was significantly classified (recognition rate 75%, p=0.04) between the 2 groups. This study of EMG and kinematics of the weapon upper limb in fencing proposes several classifications, which implies a relationship between kinematic strategies, muscular activations and fencing success.